A Comprehensive Review: Effectiveness Of Multi-Sensory Learning Strategies for Learning Disability Students - Geetika Gulati; Sangeeta Kakkar; Ritika Chauhan (International Journal of Education Sciences, 2024)
A person's ability to learn new things can be severely hampered by a range of neurodevelopmental diseases known as difficulties with learning. Multisensory learning is an instructional strategy that offers learners multiple ways to perceive information through different sensory signals. The purpose of this review is to assess how learning disabilities, Dyslexia, Dysgraphia, and Dyscalculia can be treated with a multisensory learning approach. A thorough evaluation of past papers published was done to recognize the gap by using Google Scholar, Web of Science, and Scopus between 2018 and 2023. The studies included predefined inclusion criteria that focused on implementing multisensory learning methods in learning surroundings for learning disabilities students. Multisensory learning strategies greatly enhanced academic performance in learning-disabled students, with noteworthy improvements in reading, writing, and maths skills (mean improvement score = 25%), according to quantitative analysis. Enhanced self-esteem, better motivation, and greater student engagement were among the recurrent themes retrieved in the qualitative analysis. This review offers strong evidence for learning disability students that multisensory learning approaches are beneficial. The findings encourage the wider use of multisensory approaches in learning environments to serve a varied student body better. Furthermore, the research highlights the possibility of doing additional studies on certain multimodal approaches customized for individual learning difficulties, indicating a need for individualized educational interventions. This thorough analysis emphasizes how crucial multimodal learning is to create a welcoming and encouraging learning environment for all students.
Keywords: Learning disabilities; academic performance; dyslexia; educational approach; individualized educational interventions; multisensory learning